Analisis Pencatatan Keuangan Guna Mendukung Implementasi ISAK No. 35 pada Masjid Jami’ Al-Jadid Kelurahan Simpang Rimbo, Kecamatan Alam Barajo, Kota Jambi - M. Azharudin Nur Almaris; Mohammad Orinaldi; Muthmainnah Muthmainnah (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
This study aims to determine how the application of ISAK No. 35 as a standard for financial reporting of non-profit organizations at the Al-Jadid Jami' Mosque. This study uses qualitative methods to present information, facts, and data from financial reporting applied by the Al-Jadid Jami' Mosque, with data collection methods namely observation, interviews, and documentation and ended with the reconstruction of the Al-Jadid Jami' Mosque financial report according to ISAK No. 35. From the results of this study it was found that: (1) Financial recording carried out at the Al-Jadid Jami' Mosque is still very simple and does not yet have financial accounting standards for non-profit entities, namely ISAK No. 35, the recording process is merely recording inflow and outflow, then announced by the mosque administrators to the community every Friday. (2) Obstacles faced by the Al-Jadid Jami' Mosque Administrators in presenting financial reports are the lack of understanding of the Administrators Regarding Accounting, the mosque administrators do not come from an accounting background. (3) In presenting financial reporting at the Al-Jadid Jami' Mosque according to ISAK no. 35, after the reconstruction, the results were obtained in the form of a comprehensive income report, financial position report, cash flow report, net asset change report, and notes to the financial report.